BANK SYARIAH DALAM PERSPEKTIF HUKUM EKONOMI ISLAM - Shofil Fikri; Tri Wahyuningsih; Aura Nafisa Athaya (Tarbawi, 2023)
Islamic banks are based on the philosophy of the Islamic economic system, have a variety of financial products and financial services available to the public, offering the right alternative choice for all interested parties to conduct business according to the rules of Islamic Sharia. including the provision of financing and profit-sharing financing. Sharia principles prohibit carrying out financial activities that include usury, maisyir, gharar, and buying and selling haram goods. In the process of profit sharing between customers and banks, the percentage between the two parties or mudharabah contract is based on the mudharabah contract used by Islamic Banks and UUS to raise funds for deposits, savings or other forms of investment. There is no interest system or compound interest in the Islamic banking system. In return, banks offer profit sharing based on the company's financials.